Seismic Interpretation and Reservoir Evaluation Utilizing 2-D Seismic Data and Wireline Logs of Bijnot-01 Well, Fort Abbas Field, Central Indus Basin, Pakistan : Seismic Interpretation and Reservoir Evaluation Utilizing 2-D Seismic Data and Wireline Logs of Bijnot-01 Well, Fort Abbas Field, Central Indus Basin, Pakistan - Muhammad Adnan Khan; Hamad-ur-Rahim; Syed Waqas Haider; WaqarAhmadh (International Journal of Economic and Environmental Geology, 2017)
Present study attempts to decipher the subsurface structure and reservoir characterization of Fort-Abbas field, located in Punjab platform, Central Indus Basin utilizing 2-D seismic and wireline logs data. Four seismic lines, 944-FABS-42, 944-FABS-43, 944-FABS-48, 944-FABS-49 and wireline logs of Bijnot-01 well have been used for this research work to delineate subsurface structures and demarcation of zone having fair potential of hydrocarbon accumulation. Formation evaluation for hydrocarbon potential using the reservoir properties is also the foremost objective of this research work. Based on the results of seismic data interpretation of Fort-Abbas field and integrating it with formation tops and wireline logs data, three prominent reflectors have been marked i.e. Eocene Sui Main Limestone, Cretaceous Lower Goru and Jurassic Chiltan Limestone. The structure of the area is interpreted as gently dipping monocline. Based on the breakup of reflectors on seismic section, one normal fault is marked. Time and depth contour maps are generated to demarcate lateral extension and closure of the reservoir. Based on interpretation of wireline logs, a zone has been marked from depth of 504 m to 594 m (Datta Formation) as a favorable zone having good potential for hydrocarbon accumulation. Saturation of hydrocarbon (Sh) in this zone is calculated as 57%. Keywords: 2-D Seismic, Punjab platform, Fort Abbas field, petrophysics, wireline logs.